2018
DOI: 10.1080/15548627.2018.1436936
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial effect of IFNG (interferon gamma)-induced autophagy depends on HMOX1 (heme oxygenase 1)-mediated increase in intracellular calcium levels and modulation of PPP3/calcineurin-TFEB (transcription factor EB) axis

Abstract: IFNG (interferon gamma)-induced autophagy plays an important role in the elimination of intracellular pathogens, such as Mycobacterium tuberculosis (Mtb). However, the signaling cascade that leads to the increase in autophagy flux in response to IFNG is poorly defined. Here, we demonstrate that HMOX1 (heme oxygenase 1)-generated carbon monoxide (CO) is required for the induction of autophagy and killing of Mtb residing in macrophages in response to immunomodulation by IFNG. Interestingly, IFNG exposure of macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 96 publications
(138 reference statements)
3
27
1
Order By: Relevance
“…This finding suggested that TFEB translocated to the nucleus at the early stage of ischemia through the activation of PPP3/ calcineurin. In fact, PPP3/calcineurin activation has been reported to respond to ischemic conditions in OGD-induced neuronal death [41],[] and PPP3/calcineurin-dependent TFEB nuclear translocation [42] is involved in the induction of autophagy [43,44]. The data here confirmed the potential of PPP3/calcineurin to regulate TFEB function after ischemic stroke.…”
Section: Discussionsupporting
confidence: 82%
“…This finding suggested that TFEB translocated to the nucleus at the early stage of ischemia through the activation of PPP3/ calcineurin. In fact, PPP3/calcineurin activation has been reported to respond to ischemic conditions in OGD-induced neuronal death [41],[] and PPP3/calcineurin-dependent TFEB nuclear translocation [42] is involved in the induction of autophagy [43,44]. The data here confirmed the potential of PPP3/calcineurin to regulate TFEB function after ischemic stroke.…”
Section: Discussionsupporting
confidence: 82%
“…Nuclear TFEB induces lysosomal biogenesis and autophagic flux, and clearance of intracellular Mtb. The HMOX1‐dependent induction of autophagy is also observed in Mtb‐infected mice . This pathway is summarized in Fig.…”
Section: Bacterial Infectionsmentioning
confidence: 82%
“…These findings indicate that HMOX1 plays a role in protection from mycobacterial infection. In an effort to delineate the molecular mechanism of HMOX1‐mediated cellular protection, we have demonstrated that HMOX1 is required for IFN‐γ‐induced autophagy . IFN‐γ‐induced autophagy plays a crucial role in the clearance of intracellular Mtb ; however, the mechanism is poorly understood.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…TFEB is an essential transcription factor for genes involved in autophagy and lysosomal biogenesis [34]. TFEB activation is required for IFNγ-or PPARα-induced autophagy and restriction of the intracellular growth of M. tuberculosis [20,35]. However, the nuclear translocation of TFEB has not been investigated in the context of Mabc infection.…”
Section: Pparα Is Required For Nuclear Translocation Of Tfeb In Macromentioning
confidence: 99%